Optimalisasi Kelas Ibu Hamil melalui Edukasi Kesehatan, Demonstrasi PMT, dan Senam Hamil sebagai Upaya Peningkatan Pengetahuan dan Keterampilan Ibu Hamil di Kalurahan Tridadi, Sleman: Optimizing the Pregnancy Class Program through Health Education, Complementary Feeding Demonstration, and Pregnancy Exercise to Improve Pregnant Women's Knowledge and Skills in Tridadi Village, Sleman - Maya Rosvita Adi Jayanti; Devy Kurnia Ramadhani; Supartiningsih Supartiningsih (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2025)
Maternal and child health remains a major public health priority. Based on coordination with the Sleman Primary Health Center and community health volunteers in Tridadi Village, several challenges were identified, including low participation in the Pregnant Women Class Program, limited knowledge of pregnancy danger signs and appropriate complementary feeding practices, and inadequate involvement of husbands in supporting maternal health. These conditions highlight the need for community-based educational interventions that enhance both knowledge and practical skills among pregnant women and their families. This community service program aimed to improve the knowledge and skills of pregnant women through the implementation of a Pregnant Women Class Program in Tridadi Village, Sleman Regency. The program was conducted on March 15, 2025, during a single four-hour session using a community empowerment approach that integrated health education, interactive discussions, educational videos, complementary feeding (CF) demonstrations, and pregnancy exercise practice. The program involved 12 pregnant women and their husbands, with support from community health volunteers and healthcare professionals from the Sleman Primary Health Center. Program effectiveness was evaluated using pretest–posttest knowledge assessments, observation of participants’ practical skills, and participant satisfaction surveys. The average knowledge score increased from 57.5 before the intervention to 86.3 after the intervention. Participants achieved an average practical skill score of 83.3% in complementary feeding preparation and 93.8% in pregnancy exercise performance. Furthermore, participant satisfaction reached a mean score of 4.82 out of 5. The Pregnant Women Class Program effectively improved participants' knowledge and practical skills and contributed to strengthening the capacity of pregnant women and family support in promoting maternal and neonatal health at the community level.